2017
DOI: 10.1111/codi.13691
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging following neoadjuvant chemoradiation and transanal endoscopic microsurgery for rectal cancer

Abstract: MRI shows high signal intensity and thickening of the rectal wall in recurrent disease in comparison to a low signal intensity fibrotic scar in non-recurrent disease. These findings may be useful in surveillance of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
13
0
3
Order By: Relevance
“…20,21 In earlier studies, the size of the lymph nodes was used as a positive indicator of lymph node metastasis; however, previous studies have demonstrated that enlarged lymph nodes do not always indicate metastasis and may result from exaggerated inflammatory response, whereas lymph nodes of normal size can also have micrometastases. 22 Therefore, the size of lymph nodes is not the standard to distinguish benign and malignant lesions. The accuracy in this study for evaluating lymph node metastasis was 50.1%.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In earlier studies, the size of the lymph nodes was used as a positive indicator of lymph node metastasis; however, previous studies have demonstrated that enlarged lymph nodes do not always indicate metastasis and may result from exaggerated inflammatory response, whereas lymph nodes of normal size can also have micrometastases. 22 Therefore, the size of lymph nodes is not the standard to distinguish benign and malignant lesions. The accuracy in this study for evaluating lymph node metastasis was 50.1%.…”
Section: Discussionmentioning
confidence: 99%
“…However, significant architectural changes and irregular format of these scars may be difficult to interpret during follow-up. 32 Progressive and significant increases in thickness of these scars should be indicative of possible recurrence. In this setting, baseline MR imaging scans may provide relevant information for comparison during follow-up and are strongly recommended 33 ( Fig.…”
Section: Technical Consequencesmentioning
confidence: 99%
“…MRI may be helpful in detecting recurrences and plan radical surgical salvage resection. Local recurrence after nCRT and local excision may manifest as tumor intermediate signal intensity growing along the scar [22, 80]. Inflammatory changes may overlap tumor recurrence; therefore, serial exams might help in detecting tumor-related changes (Fig.…”
Section: Restaging After Radiotherapymentioning
confidence: 99%